The nascent coffee ring: how solute diffusion counters advection. (10th August 2021) - Moore, M.R.; Vella, D.; Oliver, J.M.
Abstract: Abstract : We study the initial evolution of the coffee ring that is formed by the evaporation of a thin, axisymmetric, surface-tension-dominated droplet containing a dilute solute. When the solutal Péclet number is large, we show that diffusion close to the droplet contact line controls the coffee-ring structure in the initial stages of evaporation. We perform a systematic matched asymptotic analysis for two evaporation models – a simple, non-equilibrium, one-sided model (in which the evaporative flux is taken to be constant across the droplet surface) and a vapour-diffusion limited model (in which the evaporative flux is singular at the contact line) – valid during the early stages in which the solute remains dilute. We call this the 'nascent coffee ring' and describe the evolution of its features, including the size and location of the peak concentration and a measure of the width of the ring. Moreover, we use the asymptotic results to investigate when the assumption of a dilute solute breaks down and the effects of finite particle size and jamming are expected to become important. In particular, we illustrate the limited validity of this model in the diffusive evaporative flux regime.